Empowering Perspectives: Analyzing Gender Dynamics in International Politics - Md Amirul Islam; Mahmudul Hassan; Kutub Uddin Ahmad; Md. Bayazid Hassan (MultiTech Publisher, 2023)
This study explores the complex world of gender dynamics in global politics with the goal of empowering different viewpoints and promoting inclusive government. The introduction outlines the growing importance of gender issues in international relations and emphasizes the necessity for a thorough understanding of how they intersect with other social identities. The study's dual goals are to first investigate how gender affects political involvement and representation while taking into account how race, ethnicity, and sexual orientation interact with gender experiences. Second, to examine how gender-sensitive policies affect international efforts at development, peacekeeping, and conflict resolution. A mixed-methods strategy is used, including research using qualitative data. Findings highlight the complex ways in which gender influences international politics' power structures, decision-making procedures, and access to opportunities. The report also highlights the significance of comprehensive gender-sensitive policy and points out shortcomings in addressing intersecting identities. In order to establish a more inclusive and equitable international political scene, more research and action are required, as this study emphasizes the significance of advancing gender equity in global governance.